Gunnar Myrdals relevans för dagens sociologi: Värdepremisser och kumulativ kausalitet (Sociologisk Forskning, 1999)
Gunnar Myrdals relevance for contemporary sociology: value premises and cumulative causationGunnar Myrdal (1898-1977) is one of Sweden’s internationally most renowned social scientists. He has made important contributions to both the fields of economics and sociology, but even to the philosophy and methodology of the social sciences. M criticizes the social sciences for being value-loaded. The values built into the scientific tradition, political interests, and the personal values of the social scientist, has all a tendency to create biases in the scientific results. The only way to ”solve” this problem is that the social scientist brings the value premises that govern a study into the open. It is then possible for others to judge the conclusions reached. M has an ambition to reduce the gap between economics and sociology. For this purpose he has developed a model based on the idea of circular and cumulative causation. This model assumes that economic and non-economic factors are equally important in social processes and that the factors reinforce each other in a specific direction. M uses this model for analyzing business fluctuations, discrimination of Afro-Americans and development processes in third-world countries.